Grow a garden! - Frederick-Frost, Alexis (Maker comics., 2020)
At the Garden Gnome Academy Will, Violet, and Basil want to study exciting subjects, but instead they're stuck in Mr. Butternut's class studying composting. Includes instructions for building a compost bin and for growing vegetables from seed pots.